2017
DOI: 10.1007/s40653-017-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Victimization and Depression among Adolescents with Autism Spectrum Disorder: The Buffering Effects of Parental Mediation and Social Support

Abstract: The purpose of the present study was to examine the buffering effect of parental mediation of technology use and social support from parents on the association between cyber victimization and depression, assessed over one year. Participants were 113 7th through 9th graders from the Midwestern United States (age ranged from 12 to 17 years old; 86% were male) who were diagnosed with autism spectrum disorder. They completed questionnaires on their perceptions of parental mediation of technology use, perceived soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Parental monitoring is known to be an important protective variable as regards cyberbullying and other negative internet experiences (Baldry et al, 2019). Literature suggests that parents should find a good balance in allowing autonomy in their child's internet use, while on the other hand actively monitoring internet behavior, setting clear restrictions, and being available when the child encounters negative online experiences (Baldry et al, 2019;Faltýnková et al, 2020;Petruzelka et al, 2020;Wright, 2018). A low level of parental interest is associated with a higher chance for the child to being victimized or become a cyberbully (Baldry et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Parental monitoring is known to be an important protective variable as regards cyberbullying and other negative internet experiences (Baldry et al, 2019). Literature suggests that parents should find a good balance in allowing autonomy in their child's internet use, while on the other hand actively monitoring internet behavior, setting clear restrictions, and being available when the child encounters negative online experiences (Baldry et al, 2019;Faltýnková et al, 2020;Petruzelka et al, 2020;Wright, 2018). A low level of parental interest is associated with a higher chance for the child to being victimized or become a cyberbully (Baldry et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of digital technologies increases adolescents’ risk of cyber victimization, and research suggests that adolescents with ASD are twice as likely to be victims of cyber bullying than their peers without ASD. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Kowalski and Toth suggest tailoring cyberbullying prevention and intervention programs to group characteristics as such characteristics might increase the risk of cyberbullying victimization. In an article focusing on adolescents with autism spectrum disorder, Wright (2018) found that high levels of parental mediation of technology use and social support made the association between cyberbullying victimization and depression weaker among adolescents. She concludes that perceived social support and parental mediation of technology use reduce the risk of experiencing cyberbullying victimization and the associated depressive symptoms.…”
Section: What We Learn From the Contributions Of The Special Issuementioning
confidence: 99%
“…In the current issue, some strides are made towards filling this gap with Wright (2018) identifying that both parental mediation of technology use and social support weakened the positive link between cyberbullying victimization and depression among youth with autism spectrum disorder, and Espinoza (2018) finding that time spent with friends protects Latino adolescents from the anger, distress, and attendance problems that result from being bullied online. Given differences in culture, ability, context and a number of other factors that may differ among youth from various marginalized groups, a protective factor for one group may not necessarily be protective for another group of youth.…”
Section: Identification Of Protective Factorsmentioning
confidence: 99%